AuditRaya Mobile Information System (Siramo) at Kspps Raya Banda Madani Using Cobit 5 - Salehah, Siti Nur; Auliana, Sigit; Purnama, Eris Dwi (Merdeka Malang University, 2024)
The use of information technology at KSPPS RAYA BANDA MADANI, particularly through the Raya Mobile Information System (SIRAMO), is essential to support operations and member services. However, a thorough audit is required to ensure the security, reliability and compliance of the system to IT governance standards such as COBIT 5. This research aims to assess these aspects through an audit using COBIT 5, as well as provide recommendations for improvement.This research uses a case study method with a qualitative approach. Data was collected through interviews, questionnaires, observation, and document analysis. The results showed weaknesses in data security, information accuracy, and compliance with COBIT 5 standards, although SIRAMO supports mobile operations effectively. Recommendations for improvement include enhancing security controls, validating data, and developing more effective monitoring mechanisms. The result of this study is that audits using COBIT 5 can identify areas that need improvement to enhance the performance and security of SIRAMO at KSPPS RAYA BANDA MADANI, as well as improve operational efficiency and member satisfaction.